Takeaway Teaching - A design for redesign - Thingholm, Hanne Balsby; Larsen, Anders Hjortskov (The Danish Journal of Higher Education, 2019)
This paper introduces a new teaching design called Takeaway Teaching. The design consists of pre-designed generic themes and activities that support the development of study strategies in higher education. These themes and activities are easily redesigned by the teacher and integrated into the academic curriculum. The purpose of the design is twofold. It supports the didactic reflection and development of the teacher and the development of the students’ study competence. This paper presents the theoretical framework of the design, based on a theoretical approach of metacognition and second-order teaching and learning, and an example of a redesign of one of the generic themes; Literature Search.